Leitlinie: „HNO-spezifische Therapie der obstruktiven Schlafapnoe bei Erwachsenen“ Kurzfassung: ArGe Schlafmedizin der DeutschenGesellschaft für Hals-Nasen-Ohren-Heilkunde, Kopf- und Hals-Chirurgie = S2e-guideline: “ENT-specific therapy of obstructive sleep apnea inadults” short version : Sleep Medicine Task Force of the GermanSociety for Otorhinolaryngology, Head and Neck Surgery - Verse, Thomas; Herzog, Michael; Maurer, Joachim T.; Stuck, Boris (HNO, 2016)
The present S2e-guideline is an update of the former S2e-guideline “treatment of obstructive sleep apnea in adults”. The update was performed on behalf of the German Society for Otorhinolaryngology, Head and Neck Surgery by its Sleep Medicine Task Force. The long version of the guideline is valid from 5.9.2015 to 5.9.2020 and has been available (guideline No. 017-069) since November 2015 on the official AWMF website.The subsequently presented short version of the guideline summarizes the essentials in a legible way. For further information, please refer to the long version.
Gesehen am 20.05.2019